Reshaping the tumor microenvironment: The versatility of immunomodulatory drugs in B-cell neoplasms - Guo, Hao; Yang, Jingyi; Wang, Haoran; Liu, Xingchen; Liu, Yanyan; Zhou, Keshu (Frontiers in Immunology, 2022)
Immunomodulatory drugs (IMiDs) such as thalidomide, lenalidomide and pomalidomide are antitumor compounds that have direct tumoricidal activity and indirect effects mediated by multiple types of immune cells in the tumor microenvironment (TME). IMiDs have shown remarkable therapeutic efficacy in a set of B-cell neoplasms including multiple myeloma, B-cell lymphomas and chronic lymphocytic leukemia. More recently, the advent of immunotherapy has revolutionized the treatment of these B-cell neoplasms. However, the success of immunotherapy is restrained by immunosuppressive signals and dysfunctional immune cells in the TME. Due to the pleiotropic immunobiological properties, IMiDs have shown to generate synergetic effects in preclinical models when combined with monoclonal antibodies, immune checkpoint inhibitors or CAR-T cell therapy, some of which were successfully translated to the clinic and lead to improved responses for both first-line and relapsed/refractory settings. Mechanistically, despite cereblon (CRBN), a E3 ubiquitin ligase, was considered as the major molecular target responsible for the antineoplastic activities of IMiDs, the exact mechanisms of action for IMiDs-based TME re-education remain largely unknown. This review presents an overview of IMiDs in regulation of immune cell function and their utilization in potentiating efficacy of immunotherapies across multiple types of B-cell neoplasms.